The second record of Lasiommata petropolitana (Fabricius, 1787) in Croatia - Toni Koren; Ana Štih (Natura Sloveniae)
After the first confirmed record of L. petropolitana in Croatia on Mt Snježnik, another specimen of this species was caught on the nearby Obruč Mt in May 2010. This record expands its known area of occurrence in Croatia to the northwest and suggests that L. petropolitana could in the future be found on other mountains of Gorski Kotar and in their surrounding areas.